2022
DOI: 10.21037/atm-22-1884
|View full text |Cite
|
Sign up to set email alerts
|

G9a promotes inflammation in Streptococcus pneumoniae induced pneumonia mice by stimulating M1 macrophage polarization and H3K9me2 methylation in FOXP1 promoter region

Abstract: Background: Streptococcus pneumoniae has become a leading cause of pneumonia in recent years. Here, we investigated the mechanism of histone methylase G9a in Streptococcus pneumoniae-induced pneumonia (Spn).Methods: G9a expression in Spn mouse tissue was measured. G9a lentivirus interference vector was injected into Spn mice to evaluate the wet and dry weight of the right upper lobe and the total lung water content (TLW) and wet/dry ratio (W/D). The number of neutrophils, macrophages, and lymphocytes in bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…LPS can activate the natural immune response and secrete a large number of inflammatory cytokines, such as TNF-α, IL-6, and IL-1β, the contents of which in BALF directly reflect the degree of inflammatory response in the alveolar cavity [ 33 , 34 ]. In addition, current research has suggested that epithelial cells are also involved in regulating inflammation and lung defense, in which AT2 cells serve as one of the main sources of neutrophil chemokines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS can activate the natural immune response and secrete a large number of inflammatory cytokines, such as TNF-α, IL-6, and IL-1β, the contents of which in BALF directly reflect the degree of inflammatory response in the alveolar cavity [ 33 , 34 ]. In addition, current research has suggested that epithelial cells are also involved in regulating inflammation and lung defense, in which AT2 cells serve as one of the main sources of neutrophil chemokines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…SUV39H1/2 is linked to gene silencing and genome integrity (Li et al., 2018). G9a and GLP enhance gene transcription (Li et al., 2022; Manavi, 2022). Additionally, the accumulation and activation of SETDB1 in the nucleus suggested the formation of heterochromatin (Mutlu et al., 2018).…”
Section: Histone Modifications and Their Key Enzymesmentioning
confidence: 99%